Attitude stabilization of Marine Satellite Tracking Antenna using Model Predictive Control. (September 2021) - Wang, Yunlong; Soltani, Mohsen; Hussain, Dil Muhammad Akbar
Abstract: Attitude stabilization is a necessary function for a shipboard Marine Satellite Tracking Antenna (MSTA), which is responsible for making the antenna dish track the geostationary satellite in the presence of severe environment. A control scheme based on Model Predictive Control (MPC) is proposed to stabilize the antenna dish of an MSTA, and the detailed design process from algorithm design to Hardware-in-the-loop (HIL) simulation is explained. Due to the use of stepper motor as the actuator, the MPC is proposed to deal with the speed acceleration and deceleration problems of stepper motors, which can result in the optimal velocity profile. The MPC algorithm is implemented in Field Programmable Gate Array (FPGA) with three different data types. In addition to using traditional floating-point and fixed-point data types to represent values in MPC, a special data type, half-precision floating-point, is also explored for the first time. The comparison results are presented and analyzed in terms of FPGA resource usage and algorithm execution time. The performance of the proposed control scheme is validated in HIL simulation, which is creatively implemented in a low-cost System On Chip (SOC) FPGA. The HIL simulation results demonstrate that the proposed control scheme in fixed-point MPC can satisfy the requirements of the MSTA.